PENGARUH KELEMBAGAAN DALAM PENENTUAN UPAH NOMINAL PEKERJA PRODUKSI PADA INDUSTRI KARYA DAN PADAT MODAL - Joko Susanto (Fakultas Bisnis UKDW, 2011)
This research investigates the influence of institutional factors on wage levels of the production workers in the labor-intensive and capital intensive industries. The institutional factors include the provincial minimum wage and the union law. The data published by BPS is used in this study. This study use regression analysis based on error correction model. The results show that in the labor-intensive industries, the provincial minimum wage significantly influence the wages level of production workers, while in the capital-intensive industries the provincial minimum wage does not have effect. Meanwhile, the enforcement of union laws have no effect on the wages of production workers both in the labor-intensive and capitalintensive industries.Keywords: Minimum Wage, Union Law, Labor and Capital-Intensive Industries.